2018
DOI: 10.1002/esp.4515
|View full text |Cite
|
Sign up to set email alerts
|

What controls submarine channel development and the morphology of deltas entering deep‐water fjords?

Abstract: River deltas and associated turbidity current systems produce some of the largest and most rapid sediment accumulations on our planet. These systems bury globally significant volumes of organic carbon and determine the runout distance of potentially hazardous sediment flows and the shape of their deposits. Here we seek to understand the main factors that determine the morphology of turbidity current systems linked to deltas in fjords, and why some locations have well developed submarine channels while others d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…Recently, Pope et al () showed that a stable ice front was necessary for the formation of turbidity current channels at marine‐terminating glaciers and that large watersheds increased the likelihood of turbidity currents. Gales et al () have also shown shown that the watershed area and river discharge control the type of deltas created, that is, small Gilbert‐type deltas or deltas with long‐running channels. Our results show no significant differences between small and large watersheds on the occurrence of turbidity currents.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pope et al () showed that a stable ice front was necessary for the formation of turbidity current channels at marine‐terminating glaciers and that large watersheds increased the likelihood of turbidity currents. Gales et al () have also shown shown that the watershed area and river discharge control the type of deltas created, that is, small Gilbert‐type deltas or deltas with long‐running channels. Our results show no significant differences between small and large watersheds on the occurrence of turbidity currents.…”
Section: Discussionmentioning
confidence: 99%
“…In thick turbidites of the same system, erosion by repeated turbidity currents tended to leave only the lowermost and coarsest fraction of individual beds in the channel axis, hence any other fines are reworked (Hage et al, 2018). On an even larger scale, intrachannel erosion by upstream-migrating knickpoints has been shown to result in poor preservation potential of deposits in the channel axis, while terraces and levees were sites of enhanced deposit preservation (Gales et al, 2018). In summary, channel axes are considered to be important conveyors of and temporary storage sites for microplastics, but it is levees and terraces that are the most likely hotspots for their long-term accumulation.…”
Section: Submarine Channelsmentioning
confidence: 99%
“…The findings of this study corroborate observations from modern deepwater sediment-routing systems. Repeat bathymetric surveys and direct monitoring provide evidence for multiphase sediment-transport processes in many active unfilled canyons and slope-channel systems (Conway et al, 2012;Gales et al, 2019;Vendettuoli et al, 2019). For example, local deposition of sediment by regular turbidity currents is commonly observed in slope channels but these deposits are eventually flushed downslope during less-frequent, larger-magnitude flow events (Jobe et al, 2018;Paull et al, 2018;Stacey et al, 2019).…”
Section: Implications For Deepwater Sediment Transfer and The Role Ofmentioning
confidence: 99%